Immune responses and gut morphology in Senegalese sole (Solea senegalensis) fed dietary probiotic supplementation and following exposure to Photobacterium damselae subsp. piscicida - Barroso, Carolina; Ozório, Rodrigo O.A.; Afonso, António; Moraes, Julieta R.E. [UNESP]; Costas, Benjamín (Hindawi, 2016)
The aim of this study was to determine the effect of a dietary multi-species probiotic on growth, gut morphology and immune parameters in Senegalese sole (Solea senegalensis). Fish were fed with two experimental diets, a control diet and the same diet supplemented with the probiotic for 72 days. A sub-lethal bath challenge with Photobacterium damselae subsp. piscicida was performed after the growth trial. Intestine and blood samples were collected to study gut structure and plasmatic immune parameters. No significant differences were found in growth performance. The analysis of gut morphology showed a significant increase in intestinal villi height of Senegalese sole fed the probiotic. Regarding circulating leucocytes, dietary probiotic supplementation increased thrombocytes levels whereas a decrease in the proportion of lymphocytes was observed. No significant differences were observed in humoural immune parameters. Bath challenge differentially affected leucocyte counts and increased peroxidase activity. This study presents the possibility of using dietary probiotic supplementation to increase Senegalese sole welfare since gut morphology was positively affected. Although the immune response after a bacterial challenge was not modulated by dietary treatment, further studies would be instrumental to unravel eventual dietary benefits on immune mechanisms.
Keywords: Solea senegalensis; Bath challenge; Growth; Immunity; Intestinal structure; Probiotics